PROLIFERASI LEMBAGA-LEMBAGA PENEGAK HUKUM PADA ERA REFORMASI DALAM SISTEM KETATANEGARAAN INDONESIA (Lex Jurnalica, 2018)
AbstractAmendment of the 1945 Constitution of the State of the Republic of Indonesia (UUD 1945) has regulated the mechanism of administration of state administration related to legislative, judicial and executive relations in a balanced manner. Or in other words, there is a check and balances relationship between the three institutions. Judicial power according to the 1945 Constitution in Indonesia is implemented by a Supreme Court (MA) and by a Constitutional Court (MK). In addition to the Supreme Court and the Constitutional Court as a state law enforcement agency, also the Judicial Commission (KY) whose functions relate to the judicial power, there are other law enforcement agencies, namely the Corruption Eradication Commission (KPK) and the Financial Transaction Reports and Analysis Center (PPATK). Each authority of the executing agency and state institutions whose functions relating to the judicial power is determined by the 1945 Constitution and the laws and regulations. With the many systems of law enforcement countries born after the Reform Era has implications in the relationships between state institutions of law enforcement in carrying out their primary duties and functions. Therefore, it is necessary to consider the restructuring of the authority of the system of the judicial bodies as well as the law enforcement agencies whose duties are related to the legal authorities. Keywords: law enforcement, proliferation, reform era AbstrakPerubahan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 (UUD 1945) telah mengatur mekanisme penyelenggaraan ketatanegaraan yang terkait dengan hubungan kekuasaan legislatif, yudikatif dan eksekutif secara seimbang. Atau dengan kata lain, terdapat hubungan check and balances antara ketiga lembaga tersebut. Kekuasaan kehakiman menurut UUD 1945 di Indonesia dilaksanakan oleh sebuah Mahkamah Agung (MA) dan oleh sebuah Mahkamah Konstitusi (MK). Selain MA dan MK sebagai lembaga negara penegak hukum, juga Komisi Yudisial (KY) yang fungsinya terkait dengan kekuasaan kehakiman, ada lembaga negara penegak hukum lainnya, yaitu Komisi Pemberantasan Korupsi (KPK) dan Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK). Masing-masing kewenangan lembaga pelaksana dan lembaga negara yang fungsinya terkait dengan kekuasaan kehakiman tersebut ditentukan oleh UUD 1945 dan peraturan perundang-undangan. Dengan banyaknya lembaga negara penegak hukum yang lahir setelah Era Reformasi berimplikasi dalam hubungan antar lembaga negara penegak hukum dalam menjalankan tugas pokok dan fungsinya. Oleh karena itu, perlu dipertimbangkan adanya penataan kembali terhadap kewenangan lembaga pelaku kekuasaan kehakiman maupun lembaga penegak hukum yang fungsinya terkait dengan kekuasaan kehakiman. Kata kunci: penegak hukum, prolifrasi, era reformasi